2022
DOI: 10.1111/jdv.18134
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the dynamic changes in vitiligo: reliability and validity of the Vitiligo Disease Activity Score (VDAS) and Vitiligo Disease Improvement Score (VDIS)

Abstract: Background The assessment of the individual evolution of vitiligo is important for therapeutic decision making in daily practice. A fast, simple and validated physician-reported score to assess clinical changes in depigmentation over time in separate parts (activity and improvement) is currently missing.Objective The main objective of the study was to develop and validate the Vitiligo Disease Activity Score (VDAS) and Vitiligo Disease Improvement Score (VDIS).Methods The Vitiligo Disease Activity Score (VDAS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…For a long period of time, reliable, valid, and feasible ClinROMs to assess and quantify disease activity in vitiligo were lacking. Based on this need, several vitiligo disease activity tools were introduced and are described below 5,7,12–14,18,21–23 …”
Section: Resultsmentioning
confidence: 99%
“…For a long period of time, reliable, valid, and feasible ClinROMs to assess and quantify disease activity in vitiligo were lacking. Based on this need, several vitiligo disease activity tools were introduced and are described below 5,7,12–14,18,21–23 …”
Section: Resultsmentioning
confidence: 99%
“…4. Vitiligo Disease Activity score (VDAS) 33 : This is a subjective scoring system but it depends on patient recall and is subject to recall bias. A recent study found the VDAS and VDIS to be valid, reliable, and feasible instruments to score the evolution of vitiligo lesions.…”
Section: Confetti Lesionsmentioning
confidence: 99%
“…In clinical practice, disease activity is usually based on dynamic changes over time, potentially assisted by standardized scoring systems (e.g., VDAS and VDIS). 8 However, clinical visible signs can serve as a user-friendly, noninvasive marker for assessing disease activity in vitiligo at one specific time point. 23 A systematic review investigated the link between visible skin signs and disease activity, based on 46 articles.…”
Section: Part 1: Clinical Signsmentioning
confidence: 99%
“…Recently, the Vitiligo Disease Improvement Score (VDIS) and Vitiligo Disease Activity Score (VDAS) are developed and allow the physician to evaluate the improvement (VDIS) and worsening (VDAS) of the vitiligo, based on two specific moments while maintaining location-specific information. 8 A previously published protocol can guide the physician and researcher in taking standardized photographs. 9 At present, different new therapies are under investigation, based on targeting immune response regulatory pathways such as Janus kinase (JAK) inhibitors, 10 stressing the need for a valid marker for disease activity.…”
mentioning
confidence: 99%